Efficient photodecomposition of 2, 4-dichlorophenol on recyclable phase-mixed hierarchically structured Bi2O3 coupled with phosphate-bridged nano-SnO2. Issue 5 (12th April 2017) - Sun, Ning; Qu, Yang; Chen, Shuangying; Yan, Rui; Humayun, Muhammad; Liu, Yanduo; Bai, Linlu; Jing, Liqiang; Fu, Honggang
Abstract : 2, 4-Dichlorophenol could be efficiently photodecomposed on as-fabricated recyclable phase-mixed hierarchically structured Bi2 O3 coupled with phosphate-bridged nano-SnO2 . Abstract : In this work, phase-mixed hierarchically structured Bi2 O3 as an efficient visible-light photocatalyst for degrading 2, 4-dichlorophenol (2, 4-DCP) has been successfully fabricated using (BiO)2 CO3 as the precursor. Its exceptional photocatalytic activity is mainly attributed to the high charge separation due to the phase-mixed composition and the large surface area due to the hierarchical structure. Moreover, the photogenerated charge separation of the resulting Bi2 O3 could be further enhanced by coupling with nanocrystalline SnO2, especially the phosphate-bridged one, mainly based on the surface photovoltage responses and the fluorescence spectra related to the formed hydroxyl radical amounts. This leads to the more obviously improved visible-light activities. It is confirmed that the enhanced charge separation is attributed to the effective transfer of excited high-energy-level electrons from Bi2 O3 to SnO2 by means of electrochemical impedance spectroscopy and photocurrent action spectroscopy. Interestingly, it is shown that the as-prepared Bi2 O3, especially that coupled with the phosphate-bridged nano-SnO2, exhibits much higher photocatalytic activities under UV-vis irradiation than P25 TiO2, along with superior mineralization and recovery features. The resulting degradation reaction constant is about 6 times higher than that on P25 TiO2, and even 50 times higher if the surface area is considered. Furthermore, it is demonstrated through the radical-trapping experiments, detected main intermediates and mineralized chloride amounts that the photogenerated holes and the formed ˙O2 − could respectively dominate the photocatalytic decomposition of 2, 4-DCP on Bi2 O3 -based nanocomposites and P25 TiO2, with different possible decomposition paths suggested.